Soil Carbon Sequestration and Crop Production Course Module - Agyare, Wilson Agyei; Amponsah, William; Forkuo, Eric Kwabena; Opoku, Andrews; Quansah, Emmanuel; Bessah, Enoch; Asare, Da-Costa Mensah; Awuah, Akua Osaa; Diallo, Yacouba; Adeyewa, Debo (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The aim of this course is to develop skills in soil carbon (SC) estimation and Soil Carbon Sequestration (SCS) methods/techniques to reduce GHG emissions for sustainable crop production systems. At the end of the module participants will be able to: explain soil properties and concepts relevant to SCS; apply relevant skills for sustainable soil and crop management in a changing climate; assess climatic factors that affect soil carbon sequestration processes; develop relevant skills for the measurement and monitoring of soil carbon; apply different techniques for the sequestration of soil carbon; estimate the spatial distribution of soil carbon; and model SOC using empirical / process-based approaches.